Strategi Pengendalian Sistem dalam Sistem Informasi untuk Optimalisasi Kinerja Perusahaan - vika agustina, prafasta; Dwi Novaria Misidawati (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
ABSTRACT: An information system is a combination of various technological components that work together to produce information to support communication within an organization. The management control system is used to convey useful information in assessing performance and making effective and efficient decisions to achieve company goals. This research aims to explore the importance of system control strategies in information systems for optimizing company performance. The method used is a literature study with data sources from books, scientific journals, articles and research reports. The research results show that the control system in optimizing company performance plays an important role in implementing company strategy by motivating members to achieve company goals, besides that users of management information systems are also proven to increase operational efficiency and support better decision making.